Various Tastes of Sugar: The Potential of Glycosylation in Targeting and Modulating Human Immunity via C-Type Lectin Receptors - Busold, Stefanie; Nagy, Noémi A.; Tas, Sander W.; van Ree, Ronald; de Jong, Esther C.; Geijtenbeek, Teunis B. H. (Frontiers in Immunology, 2020)
C-type lectin receptors (CLRs) are important in several immune regulatory processes. These receptors recognize glycans expressed by host cells or by pathogens. Whereas pathogens are recognized through their glycans, which leads to protective immunity, aberrant cellular glycans are now increasingly recognized as disease-driving factors in cancer, auto-immunity and allergy. The vast variety of glycan structures translates into a wide spectrum of effects on the immune ¬system ranging from immune suppression to hyper-inflammatory responses. CLRs have distinct expression patterns on antigen presenting cells (APCs) controlling their role in immunity. CLRs can also be exploited to selectively target specific APCs, modulate immune responses and enhance antigen presentation. Here we will discuss the role of glycans and their receptors in immunity as well as potential strategies for immune modulation. A special focus will be given to different dendritic cell (DC) subsets as these APCs are crucial orchestrators of the immune response in infections, cancer, auto-immunity and allergies. Furthermore we will highlight the potential use of nanoscale lipid bi-layer structures (liposomes) in targeted immunotherapy.